2015
DOI: 10.1016/j.aorn.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nursing Care by Understanding the Bariatric Patient's Journey

Abstract: Patients who undergo obesity-related bariatric surgery seek a lasting solution to weight loss and a desire for a healthier lifestyle. Perioperative nurses should be prepared to provide sensitive, high-quality care to this population. Effective assessment and management of bariatric patients involves understanding the motivating factors for seeking bariatric surgery, such as to address the stigma and health problems associated with obesity. Nurses should be knowledgeable about expected outcomes of bariatric car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
7
0
4
Order By: Relevance
“…[14] Encourages knowledge sharing (including benefits, risks and challenges) and allows for greater advocacy in health for the patient. [15,16] In this study, it was observed that the preoperative education with group approach makes it possible to deepen the dialogue with the active participation of those involved in the process. Allows participants to express their opinions, concepts and impressions about the proposed theme, in addition to work reflexively group manifestations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[14] Encourages knowledge sharing (including benefits, risks and challenges) and allows for greater advocacy in health for the patient. [15,16] In this study, it was observed that the preoperative education with group approach makes it possible to deepen the dialogue with the active participation of those involved in the process. Allows participants to express their opinions, concepts and impressions about the proposed theme, in addition to work reflexively group manifestations.…”
Section: Discussionmentioning
confidence: 91%
“…Knowledge after Group Discussion Patients informed, motivated and accountable interact more effectively with health professionals and strive to perform actions that produce health outcomes, [20] becoming more aware of the operational risks and are more quiet and more willing to adhere to the post-operative care. [15,16] For the Pan-American Health Organization (PAHO), the empowerment of patients is essential with the support of care goals, freedom in solving problems and participation in clinical decision-making processes along with the health team. [21] Nurses play a key role in the care of patients undergoing bariatric surgery both preoperatively and postoperatively.…”
Section: Temas Themes Relatos Reportsmentioning
confidence: 99%
“…Neil and Roberson [13] explored patients who undergo obesity-related bariatric surgery and found to be three main motivating categories for weight loss: psychological, medical, and quality of life. This study indicated that the nurse often is the key point of contact and main care provider during all per operative phases for patients undergoing bariatric surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study indicated that the nurse often is the key point of contact and main care provider during all per operative phases for patients undergoing bariatric surgery. The must be well informed of the patients' motivating factors, as well as the patients' multiple-step preparation for surgery, so that the patients can be well informed, motivated, and cognizant of the operative risks [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Factors that can affect patients’ decisions to undergo surgery include financial stability, opinions of health care providers, perceptions of bariatric surgery, comorbidities, and family member support . Additionally, preoperative requirements for a psychological evaluation; nutritional counseling; documented attempts at weight loss; and, in some circumstances, costly screenings, such as sleep studies or cardiac clearances, create a complicated presurgical approval process for patients . Although the literature indicates that choosing to undergo bariatric surgery is a complex decision, evidence regarding the ways that families influence patients’ decisions is lacking.…”
mentioning
confidence: 99%